(untitled) (TAMADDUN NURI JURNALI, 2025)
This article mainly discusses the psychological state and attitude that arise as a result of the complex nature of the doctor-patient relationship. The article describes the medical and tactical foundations of various mental states experienced by a patient. In particular, the doctor’s use of complex medical terms and their analysis based on his in-depth knowledge are scientifically substantiated.